An Ordinance in the Revision of the Ordinances Governing the City of Kansas, p. 264-65, ch. 34, § 3 - (:unkn) unknown (General Publisher, 1880)
No person shall, in this city, wear under his clothes or concealed about his person, any pistol or revolver, except by special permission from the Mayor; nor shall any person wear under his clothes, or concealed about his person, any slung-shot, cross knuckles, knuckles of lead, brass or other metal, or any bowie knife, razor, billy, dirk, dirk-knife or dagger, or any knife resembling a bowie knife, or any other dangerous or deadly weapon. Any person, violating any provision or requirement of this section, shall be deemed guilty of a misdemeanor, and, upon conviction thereof before the City Recorder, shall be fined not less than fifty dollars nor more than five hundred dollars
--
Keywords: CARRY - CONCEALED